Interference characteristics and suppression techniques in power line communication - Gaojing ZHANG; Xingzhong XIONG (Dianxin kexue)
Power line can provide electrical energy to the electric equipment，and it can also be used as a communications system for transmitting information. The reliable and efficient information transmission is the basic requirement of any kind of communication network. Based on the research of dynamic load impedance characteristic effects，attenuation characteristics of multipath effect and impulse noise interference characteristics，the feasibility of several typical inhibition technologies were analyzed，from perspective of the physical layer signal processing and the data link layer data transmission，which provided valuable reference for exploring effective technologies of pulse interference suppression in the power line communication.